Application of Bamboo Reinforcement in Beam Design - Azuaha, Nurul Sahirah; Mad Kalam, Aisyah Fatimah; Darwis, Nur Najlah Najwa Dasima; Mohammad Yazid, Nornajihah; Salim, Salman (Multidisciplinary Applied Research and Innovation, 2023)
Bamboo has a weaknesses which are vulnerable to bamboo-decay, fungal attack and shrinkage issue. The aim of this project is to apply bamboo in reinforcement in design beam. Hence, the study is conducted by designing a concrete beams using reinforcement treated bamboo strips. The bamboo went through the cutting process with the specifications required. The bamboo is cut into strips with 900 mm length and 20m width before been preserved in boric acid and borax solution. Then, this project is carried out with evaluation of a flexural strength of bamboo reinforced concrete beams according to the BS. The evaluation of bamboo’s flexural strength is identified by doing the test using the Flexural Testing Machine. In addition, this study also is to analyse the strength of concrete beams between bamboo strips treated reinforcement and steel reinforcement concrete beams. The analysis is done by doing the test to identify the difference of deflection value of both different percentages of beams, which are 100% steel reinforced concrete and 100% bamboo reinforced concrete. The findings found that, the strength of bamboo reinforced concrete is equivalent to the steel reinforced concrete since the maximum deflection of both beams increases when the value of ultimate load increases. In a conclusion, bamboo can be considered, as a construction material seems it has better benefits compare to other standard materials as example bamboo provides safe environment and free chemical. The initiative of using bamboo should be increased in Malaysia due to more eco-friendly and the benefits in future.